MAPPING TREND IMPLEMENTASI STRATEGI PROMOSI DESA WISATA KEMBANGARUM TURI SLEMAN YOGYAKARTA - Yulianto, Atun; Mayasari, Citra Unik (Sekolah Tinggi Pariwisata AMPTA, 2018)
Kabupaten Sleman has many tourist attraction objects that can be used as tourist destinations for anyone. The attraction of this city includes the panorama of nature, history, museums, culture, ancient relics, culinary and tourist villages. The number of tourist villages in Sleman regency is in accordance with the data of the Sleman Regency Culture and Tourism Office (Fauzy & Putra, 2015), as many as 38 tourist villages. The tourism village management base generally involves many parties, including by empowering local communities as local communities who play an active role in managing and developing tourism villages. However, according to (Damanik, 2013),